2009
DOI: 10.1097/coh.0b013e32832f00c0
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-specific antibody responses during acute and chronic HIV-1 infection

Abstract: Purpose of review The humoral immune response to HIV-1 throughout infection is comprised of complex mixtures of antibody isotypes with numerous HIV-1 specificities. However, unlike antibody responses to most infections, protective antibody responses are delayed and do not arise until long after HIV-1 latency is established. We review recent data on HIV-1-specific antibody isotypes induced following HIV-1 transmission: to understand the effects of HIV-1 on B cell and T cell effector responses, to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 68 publications
11
138
0
2
Order By: Relevance
“…45 However, memory B-cell responses are also important to consider, both for vaccine development and ability of the immune system to control HIV in infected individuals. Several studies have demonstrated that the maintenance of HIV-specific antibodies and memory B cells is dependent on the presence of HIV antigen.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, memory B-cell responses are also important to consider, both for vaccine development and ability of the immune system to control HIV in infected individuals. Several studies have demonstrated that the maintenance of HIV-specific antibodies and memory B cells is dependent on the presence of HIV antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of these cytokines might promote an earlier development of autologous neutralizing antibodies that may contribute to faster and long-lasting control of HIV. 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…There has been much work published using the 2 nd route (Myron S. Cohen 2007;Margoli 2009), albeit they offer us a view into the post active viremia stage, leaving us in the dark as to the earliest days post infection. Such studies (Tomaras and Haynes 2009) have revealed that there is early destruction of B cell generative microenvironment, and that this might be one of the causes for a delay in protective anti HIV antibody responses (Richman et al 2003;Davis et al 2009;Stacey et al 2009) and other parameters of antibody response (Tomaras et al 2008). Polyclonal cell activation in early HIV infection and loss of gut germinal centres have been observed (Levesque et al 2009).…”
Section: Immunological Findings Of the Early Stages Of Infectionmentioning
confidence: 99%